THE EFFECT OF OIL PRICES ON INFLATION - Ali, Syed Umair Ali (Informative Journal of Management Sciences (IJMS), 2022)
The fluctuation in oil prices enhances the inflation rate and disturbs the business cycle and economic growth as well. The government put all efforts to reduce the dependency of economic growth on oil prices. The study aims to examine the impact of oil price fluctuation on economic growth which ultimately results in a high inflation rate. The statistical results obtained from SPSS depict that. Oil price fluctuations are highly correlated with each other and a sudden rise in the prices of oil increases the price of all products. The price rise reduces the demand at local and international levels which ultimately results in a high inflation rate. Time and lack of availability of literature are the major limitations of the research. The conclusion was drawn that, the government must design the policies to reduce the impact of oil price variations on the economy. it is concluded that the fluctuation in oil prices results in a high inflation rate. Although, other factors such as GDP and per capita income play a role in the economic development of the country the fluctuation in prices results in the recession and economic downturn